Improving primary education, the vital role of pedagogical technologies - Jalaldinova Madinakhan Khojakanovna (Genius Journals, 2024)
In the modern educational environment, the integration of pedagogical technologies has emerged as a transformative force in improving the effectiveness of primary education. This article argues that pedagogical technologies play an important role in developing engaging, personalized, and interactive learning experiences for young learners. By exploring the benefits and challenges associated with technology integration in primary education, this paper seeks to highlight the importance of using these tools to create a dynamic and inclusive learning environment that meets the diverse needs of students.
Keywords: pedagogical technologies; primary education; digital education